Ultrahigh thermal rectification based on near-field thermal radiation between dissimilar nanoparticles. (September 2019) - Wen, Shizheng; Liu, Xianglei; Cheng, Sheng; Wang, Zhoubing; Zhang, Shenghao; Dang, Chunzhuo
Highlights: Thermal rectification ratios more than 10, 000 are theoretically demonstrate. Rectification ratios are insensitive to the variation of gap distances. Shapes of nanoparticles can be used to regulate thermal rectifications. Abstract: The capability of manipulating heat flux at the nanoscale has many promising applications in modern electronics and information processing industries. In this paper, a design to achieve ultrahigh thermal rectification is proposed based on near-field thermal radiation between nanoparticles made of intrinsic silicon and a dissimilar material. A record-high rectification ratio of more than 10 4 is theoretically demonstrated, and the underlying mechanism lies in the prominent increase of imaginary part of dielectric function of intrinsic silicon induced by thermally excited electrons at high temperatures. Effects of gap distances, materials and configurations of nanoparticles on the rectification ratio are also investigated. This work may pave the way for the design of efficient thermal diodes, thermal transistors, and other thermotronics devices.